Symbiotic Life of Echinoderm Larvae - Carrier, Tyler J.; Reitzel, Adam M. (Frontiers in Ecology and Evolution, 2020)
Echinoderms larvae have served as a fundamental system for understanding development and life history evolution over much of the last century. In the last few decades, our understanding of echinoderm larvae has expanded to the microbiota that they associate with. These symbionts and the communities that they form in relation to echinoderm larval host is the focus of this review. Our synthesis of the literature suggests three primary themes. First, larval echinoderms associate with ‘subcuticle bacteria’ that appear to colonize select tissue types. Second, the bacterial communities associated with larval echinoderms exhibit compositional shifts that are correlated with several fundamental properties of larval biology (e.g., development and morphological plasticity) and ecology (e.g., feeding environment). Third, echinoderm larvae exhibit specific responses to pathogenic bacteria that may aid in maintaining the symbiont community and avoid dysbiosis. To our knowledge, no studies have focused on whether climate-related stressors impact the composition of these symbiont communities or how changes in bacteria may modulate response by larvae to these environmental stressors. Lastly, we conclude by outlining techniques that need to be established in echinoderm larvae to transition from correlations between larvae and their associated microbiota to the function of these symbionts.